1978
DOI: 10.1128/jb.133.3.1282-1286.1978
|View full text |Cite
|
Sign up to set email alerts
|

Glucose metabolism and dimorphism in Mucor

Abstract: Mucor racemosus fermented glucose to ethanol, carbon dioxide, and glycerol. When this fungus was grown anaerobically in either the yeast or mycelial form, the catabolism ofglucose was very similar. Yeast cells shifted to aerobic conditions maintained a high flux of glucose carbon through the glycolytic and pentose phosphate pathways. Mycelial cells grown aerobically catabolized glucose in a manner consistent with a respiratory metabolism. Although there was no consistent pattern of glucose metabolism in the my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

1980
1980
2007
2007

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…Many studies had been reported concerning the relationship between the metabolic mode and morphogenesis in Mucor species (3,6,10,13,18,22). The reports are in agreement that yeast development invariably correlates with an increased capacity for fermentative metabolism.…”
mentioning
confidence: 60%
“…Many studies had been reported concerning the relationship between the metabolic mode and morphogenesis in Mucor species (3,6,10,13,18,22). The reports are in agreement that yeast development invariably correlates with an increased capacity for fermentative metabolism.…”
mentioning
confidence: 60%
“…Fermentative metabolisn and lower P.'s predominate during the later growth of these cells. Low Ps's were observed in cells growing in C02 and were correlated with the lowered glycolytic rates evident in these cells (10). The extent of ribosome phosphorylation, therefore, may be positively correlated with the rate of ATP production and negatively correlated with the rate of energy comsumption.…”
Section: Resultsmentioning
confidence: 90%
“…1). In either anaerobic yeasts or microaerobic mycelia and in C02-grown yeasts polypeptides 4,5,6,10,13,14,18,20,22,23,25,27,28,29,32,34,36,41,49, and 52 were exclusively present or present in greater amounts in the oxygen-depleted cells (CO2 sparged, microaerobic or anaerobic) when compared with the aerobically grown cells. Thus, considerable qualitative and quantitative differences exist between O2-deprived cells and aerobic cells irrespective of the morphology of the cells.…”
Section: Resultsmentioning
confidence: 96%
“…C02-grown yeast cells had a doubling time of 4 h, while aerobic cells doubled every 1.5 h (data not shown). In addition, it has been shown that these cells differ in carbon catabolism, in terms of flux and distribution through fermentative and oxidative metabolic pathways (5). Therefore, comparison of these two figures cannot differentiate polypeptides unique to one morphology from those that reflect metabolicand growth-dependent differences between the cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation